Gut Mucosal Gene Expression and Metabolic Changes After Roux‐en‐Y Gastric Bypass Surgery. Issue 11 (5th November 2020) - Jorsal, Tina; Christensen, Marie M.; Mortensen, Brynjulf; Nygaard, Eva B.; Zhang, Chen; Rigbolt, Kristoffer; Wandall, Erik; Langholz, Ebbe; Friis, Steffen; Worm, Dorte; Floyd, Andrea; Helgstrand, Frederik; et al.
Abstract : Objective: Changes in the secretion of gut‐derived peptide hormones have been associated with the metabolic benefits of Roux‐en‐Y gastric bypass (RYGB) surgery. In this study, the effects of RYGB on anthropometrics, postprandial plasma hormone responses, and mRNA expression in small intestinal mucosa biopsy specimens before and after RYGB were evaluated. Methods: In a cross‐sectional study, 20 individuals with obesity undergoing RYGB underwent mixed meal tests and upper enteroscopy with retrieval of small intestinal mucosa biopsy specimens 3 months before and after surgery. Concentrations of circulating gut and pancreatic hormones during mixed meal tests as well as full mRNA sequencing of biopsy specimens were evaluated. Results: RYGB‐induced improvements of body weight and composition, insulin resistance, and circulating cholesterols were accompanied by significant changes in postprandial plasma responses of pancreatic and gut hormones. Global gene expression analysis of biopsy specimens identified 2, 437 differentially expressed genes after RYGB, including changes in genes that encode prohormones and G protein–coupled receptors. Conclusions: RYGB affects the transcription of a wide range of genes, indicating that the observed beneficial metabolic effects of RYGB may rely on a changed expression of several genes in the gut. RYGB‐induced changes in the expression of genes encoding signaling peptides and G protein–coupled receptors may disclose new gut‐derived treatment targets against obesity and diabetes.